Layoffs, lemons, race and gender - Luojia Hu; Christopher Taber (Institute for the Study of Labor (IZA), 2005)
This paper expands on Gibbons and Katz (1991) by looking at how the difference in wage losses across plant closing and layoff varies with race and gender. We find that the differences between white males and the other groups are striking and complex. The lemons effect of layoff holds for white males as in Gibbons and Katz model, but not for the other three demographic groups (white females, black females, and black males). These three all experience a greater decline in earnings at plant closings than at layoffs. This results from two reinforcing effects. First, plant closings have substantially more negative effects on minorities than on whites. Second, layoffs seem to have more negative consequences for white men than the other groups. We also find that the relative wage losses of blacks following layoffs increased after the Civil Rights Act of 1991 which we take as suggestive of an informational effect of layoff as in Gibbons and Katz. The results are suggestive that the large losses that African Americans experience at plant closing could result from heterogeneity in taste discrimination across firms.
Keywords: J6; J7; 330; asymmetric information; displaced workers; racial and gender wage gap; discrimination; heterogeneous human capital